PENGARUH WATER, SANITATION, AND HYGIENE (WASH) TERHADAP KEJADIAN STUNTING PADA BALITA DI INDONESIA: A SYSTEMATIC REVIEW - Ariyanti, Rea; Saefurrohim, Muhamad Zakki; Rahayu, Eka Putri (Lembaga Penelitian dan Pengabdian kepada Masyarakat STIKes Panti Waluya Malang, 2025)
Background: Stunting is still a serious public health problem, especially in developing countries like Indonesia. The incidence of stunting in children is multifactorial, one of which is thought to be caused by environmental factors such as lack of access to safe drinking water, sanitation facilities and hygiene practices (WASH). Purpose: To explore previous studies that are relevant in identifying water, sanitation, and hygiene (WASH) factors that play a role in the incidence of stunting in toddlers in Indonesia Methods: This research is a systematic review prepared based on the PRISMA flowchart method as a guide. Three electronic databases were used in the literature search, namely: Garuda Portal, Pubmed and Science Direct. Articles were selected based on publications in the last 3 years, namely from 2022-2024. Result: There were 8 articles from a total of 1,088 publications identified through three online databases that were deemed suitable for analysis. The results of the analysis show that Water (low community access to clean water and drinking water sources), Sanitation (means for disposing of feces and waste water), and Hygiene (the habit of washing hands with soap) have a significant influence on the incidence of stunting among toddlers in Indonesia. Implication: Policy makers can integrate WASH programs into programs that can support the reduction of stunting rates, such as nutrition programs, namely emphasizing the importance of clean water in food preparation, as well as educating about the relationship between poor sanitation and the risk of infection that can interfere with nutrient absorption.